NASA leadership: utilizing awe-narratives to enhance wellbeing - Thompson, Jeff (Frontiers in Space Technologies, 2025)
The wellbeing of astronauts on long-duration space missions is critical to current and future mission success. It is equally important that those who support astronauts, pre-mission, during the mission, and post-mission, are thriving as well. Therefore, this interpretative phenomenological analysis study examines how a selection of NASA leaders perceive a phenomenon, awe, along with related resilience practices, as supporting their wellbeing in both their professional work and personal lives. The results reveal that awe-narrative interviews can support them professionally while also enhancing their overall wellbeing. Awe narratives have the ability to serve as a gateway to other resilience practices, including cognitive reappraisal, finding meaning and purpose in life, gratitude, hope and optimism, and social connectedness. These results suggest the awe narrative-based interventions can offer both an evidence-based and practical way to benefit NASA personnel, as well as other professionals working in high-pressure and stressful environments.